Heritage, local development and social construction of territories. Conversation with Roberto Santana Ulloa (Revista LIDER, 2020)
Roberto Santana is a distinguished chilean social geographer. He has lived in France for thirty years, and his relationship with Latin America has remained intact all this time. He has developed ample research activities, taking geography to dialogue with other disciplines, such as sociology, anthropology, and political science. His work is characterized by its rigorousness in the characterization of social processes, actors and contexts. He is an unquenchonable reader who, from recent advances in the Social Sciences, returns many time to revisit the descriptions of territorially localized processes, amplifying the levels of comprenhension of these same processes. In this interview, Roberto Santana discusses culture, territory and developmente processes, contemplating three of his essays which are considered representative of his work.